Taking Advantage of Disposal Bamboo Chopsticks to Produce Biochar for Greenhouse Crop Cultivation - Saowanee Wijitkosum; Thavivongse Sriburi; Luechai Krutnoi (Ital Publication, 2024)
Biochar is a value-added product that can be used for many purposes, particularly for environmental and agricultural purposes. In this study, pyrolysis at 450–500 °C was used to upgrade urban waste such as disposable bamboo chopsticks (DBCs) into biochar. The properties of DBC biochar were analyzed, and the biochar was subsequently used to cultivate Romaine lettuce to assess its potential as a soil amendment. Its properties, including specific surface area (SSA), pore size, pore volume, pH, cation exchange capacity (CEC), contents of carbon (C), hydrogen (H), nitrogen (N), oxygen (O), macronutrient content, and the atomic ratio of H/C, O/C, (O+N)/C, and C/N, were analyzed. The experimental pots consisted of four treatments, each with ten replicates: unamended soil (TC), soil amended with 10% (w/w) vermicompost (TV), soil amended with 10% vermicompost mixed with 1.5% biochar (TVB1.5), and soil amended with 10% vermicompost mixed with 2.5% biochar (TVB2.5). Fundamental physicochemical soil properties and plant yield (plant height, leaf width, number of leaves, and fresh weight) were investigated. The results indicated that the DBC biochar was neutral (pH 6.80) and had a high CEC (10.86 cmol/kg), 66.80% C, 3.76% H, 25.93% O, and 0.61% N. It had mesopores (39.077 Å), a large SSA (0.542 m2/g), and a pore volume of 0.005 cc/g. The biochar exhibited high aromaticity and hydrophobicity. Based on these results, the DBC biochar has the potential to be used as a soil amendment: it significantly enhances soil quality and increases plant yields. The application of 2.5% biochar resulted in the highest yield. Doi: 10.28991/ESJ-2024-08-03-07 Full Text: PDF